2016
DOI: 10.1111/jpn.12548
|View full text |Cite
|
Sign up to set email alerts
|

Sodium in feline nutrition

Abstract: SummaryHigh sodium levels in cat food have been controversial for a long time. Nonetheless, high sodium levels are used to enhance water intake and urine volume, with the main objective of reducing the risk of urolithiasis. This article is a review of current evidence of the putative risks and benefits of high dietary sodium levels. Its secondary aim is to report a possible safe upper limit (SUL) for sodium intake. The first part of the manuscript is dedicated to sodium physiology, with a focus on the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 81 publications
(140 reference statements)
0
13
0
Order By: Relevance
“…Although there are some concerns about high sodium intake in cats, studies have shown that relatively elevated amounts of sodium in food, up to 1.1% in dry matter, did not alter the blood pressure or the renal function of these animals (Buranakarl, Mathur, & Brown, 2004;Luckschander et al, 2004;Reynolds et al, 2013;Xu, Laflamme, & Long, 2009). Additionally, in a review of the available literature for cats, including studies about the sodium effects on the risk of urolith formation, changes in the blood pressure and cardiovascular alterations or kidney diseases, the authors proposed a safe upper limit of sodium of 750 mg/MJ (Nguyen et al, 2017), an amount for which there is no evidence of any deleterious effect in some long-term studies. This proposed safe upper limit is higher than the concentrations that were tested in the present study, which varied from 405 to 550 mg/MJ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are some concerns about high sodium intake in cats, studies have shown that relatively elevated amounts of sodium in food, up to 1.1% in dry matter, did not alter the blood pressure or the renal function of these animals (Buranakarl, Mathur, & Brown, 2004;Luckschander et al, 2004;Reynolds et al, 2013;Xu, Laflamme, & Long, 2009). Additionally, in a review of the available literature for cats, including studies about the sodium effects on the risk of urolith formation, changes in the blood pressure and cardiovascular alterations or kidney diseases, the authors proposed a safe upper limit of sodium of 750 mg/MJ (Nguyen et al, 2017), an amount for which there is no evidence of any deleterious effect in some long-term studies. This proposed safe upper limit is higher than the concentrations that were tested in the present study, which varied from 405 to 550 mg/MJ.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in dietary sodium was also suggested to increase urination (Anderson, 1982;Hawthorne & Markwell, 2004), as sodium is known to increase the water renal excretion and consumption (Luckschander, Iben, Hosgood, Gabler, & Biourge, 2004;Paßlack, Burmeier, Brenten, Neumann, & Zentek, 2014a). Although some concerns are postulated about the safety of high dietary sodium intake for heart and kidney health, the scientific evidence is low with a relatively broad margin of safety to be explored (Chetboul et al, 2014;Luckschander et al, 2004;Nguyen, Reynolds, Zentek, Paßlack, & Leray, 2017;Reynolds et al, 2013). According to FEDIAF (2018), sodium levels up to 1.5% DM (3.75 g/1000 kcal ME or 0.90 g/MJ ME) are safe for healthy cats.…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen et al (2017) demonstrated that the addition of sodium significantly above levels recommended by the NRC (40 mg/MJ ME) or FEDIAF (45 mg/MJ ME) is common practice in commercial diets for cats. In the 26 products investigated, sodium content ranged from 110 mg/MJ ME in a renal diet up to 820 mg/MJ ME in a diet formulated for urolithiasis, which exceeds the safe upper limit suggested by Nguyen et al (740 mg/MJ ME) [ 75 ]. The results of a study on rats underlined this potential issue.…”
Section: Discussionmentioning
confidence: 75%
“…Calcium, phosphorus, and magnesium are associated with the development and maintenance of bones and teeth, as well as being necessary for the proper functioning of the muscular and nervous system of dogs [5]. Potassium and sodium are responsible for maintaining the electrolyte balance, regulation of body fluids, and transport of nutrients in the blood [6]. Nutritional guidelines provide minimum and, in some cases, maximum recommended Molecules 2020, 25, 5173 2 of 24 levels for the elements that are essential in a dog's diet (Ca, P, K, Na, Cl, Mg, Cu, I, Fe, Mn, Se, Zn).…”
Section: Introductionmentioning
confidence: 99%